2015
DOI: 10.1007/s12678-015-0264-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Vanadium Ions on the Degradation Behavior of Platinum Catalysts for Oxygen Reduction Reaction

Abstract: The vanadium air redox flow battery is a combination of a redox flow battery and a reversible fuel cell. For the oxygen reduction during discharge, platinum (Pt) catalysts are common. During operation, vanadium (V) cations can penetrate through a proton exchange membrane into the water/air half-cell. The aim of the present work is to study whether V compounds are deposited on the Pt surface under operation conditions or whether the V ions influence the stability of Pt in any other way. Thereby, bulk platinum e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…Previous works have reported that vanadium can enhance the electrocatalyst performance either by forming M-V (M is precious metal) alloy [19][20][21] or by surface vanadium redox species modication. 22,23 However, our results demonstrate that vanadium species are not an active part for OER, rather showing the signicant inuences on retaining the aerogel structure under atmospheric drying and lowering the impurity content of the chlorine. To the best of our knowledge, we present for the rst time the exploitation of the highly porous 3D structure of aerogel support for enhancing OER activity.…”
mentioning
confidence: 69%
“…Previous works have reported that vanadium can enhance the electrocatalyst performance either by forming M-V (M is precious metal) alloy [19][20][21] or by surface vanadium redox species modication. 22,23 However, our results demonstrate that vanadium species are not an active part for OER, rather showing the signicant inuences on retaining the aerogel structure under atmospheric drying and lowering the impurity content of the chlorine. To the best of our knowledge, we present for the rst time the exploitation of the highly porous 3D structure of aerogel support for enhancing OER activity.…”
mentioning
confidence: 69%
“…The comparison of measurements of Pt nanorods, Ir-decorated Pt (Ir@Pt) nanorods, and Ir nanodots also consisted of an activation protocol followed by an OER–ORR stability protocol simulating multiple changes between charge and discharge mode of the URFC. Because it is known that cycling between ORR and OER potentials is very degrading for Pt nanoparticles, an OER stability protocol was also carried out simulating charge–stop cycles: Activation protocol (six low-potential characterization cycles, ten wide-potential characterization cycles, six low-potential characterization cycles) OER–ORR stability protocol (2400 OER–ORR degradation cycles in groups of 50 to 200 cycles, interrupted by two wide-potential characterization cycles and six low-potential characterization cycles, respectively) Or: OER stability protocol (2400 OER degradation cycles in groups of 50 to 200 cycles, interrupted by two wide-potential characterization cycles and six low-potential characterization cycles, respectively) …”
Section: Experimental Methodsmentioning
confidence: 99%
“…One approach enabling short- and long-term energy storage as well as clean mobility is the production and consumption of hydrogen. , One technology for hydrogen production is the proton-exchange membrane water electrolyzer (PEMWE). , Usually, iridium (Ir) and ruthenium (Ru) mixed oxides are used as catalysts for the oxygen evolution reaction (OER) in the PEMWE because of the harsh conditions. Another technology combining hydrogen production and consumption in one device is the unitized regenerative fuel cell (URFC). , The OER catalyst during charging is mostly IrO 2 . As catalyst for the oxygen reduction reaction (ORR), during discharging platinum (Pt) is commonly used. , The mentioned catalysts are also used in other energy storage systems utilizing oxygen reactions like, for example, the vanadium air redox flow battery. , …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations